Galactosaminogalactan, a new immunosuppressive polysaccharide of Aspergillus fumigatus. - Thierry Fontaine (PLoS Pathogens, 2011)
A new polysaccharide secreted by the human opportunistic fungal pathogen Aspergillus fumigatus has been characterized. Carbohydrate analysis using specific chemical degradations, mass spectrometry, ¹H and ¹³C nuclear magnetic resonance showed that this polysaccharide is a linear heterogeneous galactosaminogalactan composed of α1-4 linked galactose and α1-4 linked N-acetylgalactosamine residues where both monosacharides are randomly distributed and where the percentage of galactose per chain varied from 15 to 60%. This polysaccharide is antigenic and is recognized by a majority of the human population irrespectively of the occurrence of an Aspergillus infection. GalNAc oligosaccharides are an essential epitope of the galactosaminogalactan that explains the universal antibody reaction due to cross reactivity with other antigenic molecules containing GalNAc stretches such as the N-glycans of Campylobacter jejuni. The galactosaminogalactan has no protective effect during Aspergillus infections. Most importantly, the polysaccharide promotes fungal development in immunocompetent mice due to its immunosuppressive activity associated with disminished neutrophil infiltrates.